2011
DOI: 10.1002/zaac.201100167
|View full text |Cite
|
Sign up to set email alerts
|

The First Examples of Selenidogermanate Salts with Lanthanide Complex Counter Cations: Solvothermal Syntheses and Characterizations of [{Ln(en)3}2(μ‐OH)2]Ge2Se6 (Ln = Eu, Ho) and [{Ho(dien)2}2(μ‐OH)2]Ge2Se6

Abstract: The first selenidogermanate salts with lanthanide complex counter cations (IVa, b) and (V) crystallize in the monoclinic space group P21/n with Z = 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…The soft Lewis base SbSe 4 3À binds with Ln(III) of the Ln-dien complexes to complete coordination around Ln(III), forming [Ln(dien) 2 (μ-η 1 ,η 2 -SbSe 4 )] n (1, 2) and [Ln(dien) 2 (η 2 -SbSe 4 )] (3,4). Our present and previous work have shown that the Ln 2 O 3 /polyamine (polyamine = en, dien, and trien) system is convenient sources of lanthanide(III)-polyamine complexes under solvothermal conditions [17][18][19][20][21][22][23][24][25][26][27]. Heated under a N 2 atmosphere, 1-4 lose their dien components in one step at 215-256°C.…”
Section: Syntheses and Infrared Spectramentioning
confidence: 85%
See 1 more Smart Citation
“…The soft Lewis base SbSe 4 3À binds with Ln(III) of the Ln-dien complexes to complete coordination around Ln(III), forming [Ln(dien) 2 (μ-η 1 ,η 2 -SbSe 4 )] n (1, 2) and [Ln(dien) 2 (η 2 -SbSe 4 )] (3,4). Our present and previous work have shown that the Ln 2 O 3 /polyamine (polyamine = en, dien, and trien) system is convenient sources of lanthanide(III)-polyamine complexes under solvothermal conditions [17][18][19][20][21][22][23][24][25][26][27]. Heated under a N 2 atmosphere, 1-4 lose their dien components in one step at 215-256°C.…”
Section: Syntheses and Infrared Spectramentioning
confidence: 85%
“…Recently, we have demonstrated that the solvothermal synthesis is a successful approach to ternary lanthanide chalcogenidometalates by using lanthanides instead of TMs in the solvothermal reactions, and have synthesized lanthanide(III)-containing chalcogenidogermanates [17], chalcogenidostannates [18][19][20][21], chalcogenidoarsenates [22,23], and chalcogenidoantimonates [24][25][26][27] in en or dien solvents. In the case of chalcogenidoantimonates, the Ln/Sb/Se system has been systematically investigated in en solvent across the lanthanide series and two structural types of lanthanide selenidoantimonates, Ln(en) 4 (SbSe 4 )] (Ln = La-Nd) and [Ln(en) 4 ]SbSe 4 ·0.5en (Ln = Sm-Yb), were obtained [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…3e Notably, the cations compensating for the germanium chalcogenide anionic charge are transition metal complex cations. However, germanium chalcogenides with lanthanide-containing counter cations have been less well explored under mild solvothermal conditions and limited examples include lanthanide selenidogermanates [{Ln(en) 3 } 2 (m-OH) 2 ]Ge 2 Se 6 (Ln ¼ Eu, Ho) and [{Ho(dien) 2 } 2 (m-OH) 2 ]Ge 2 Se 6 , 11 which are composed of discrete selenidogermanate [Ge 2 Se 6 ] 4À anions and dinuclear lanthanide complex cations. However, to the best of our knowledge, no thiogermanates combined with lanthanide complexes have been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…The bi-or tri-dentate chelating amines usually preferably coordinate to TM or Ln ions to form saturated complex cations, which prevent the TM or Ln amine complexes from bonding with Q (Q ¼ S, Se, Te) atoms of germanium chalcogenides anions, as exemplified by [M(en) 3 ] 2 Ge 2 S 6 (M ¼ Co, Mn, Ni), 6 [Mn(dien) 2 ] 2 Ge 2 Se 7 , 8 [Eu(dien) 3 ] 2 [Ge 2 S 6 ]Cl 2 (2, this work) [{Ln(en) 3 } 2 (m-OH) 2 ]Ge 2 Se 6 (Ln ¼ Eu, Ho) and [{Ho(dien) 2 } 2 (m-OH) 2 ]Ge 2 Se 6 11. Amines can act as a tetra-or penta-dentate molecule on at least one coordination site at the TM ion and can form a bond to the germanium chalcogenide anion to give novel…”
mentioning
confidence: 95%
“…The Ho-N bond lengths are 2.467(5)-2.513( 5) Å and are consistent with those in holmium complexes with organic amines. 17 There are many important hydrogen bonds between the -NH 2 groups of the [Ho(dap) 4 ] 3+ cations and the free Cl − ions (N-H⋯Cl). The [Ho(dap) 4 ] 3+ cations and Cl − anions are interconnected via these N-H⋯Cl interactions, forming an interesting 1-D helical chain (Fig.…”
Section: Resultsmentioning
confidence: 99%